PERAN MEDIASI KEPUASAN KERJA PADA PENGARUH KETERIKATAN KERJA TERHADAP KINERJA SUPERVISOR HERBALIFE GRESIK - Dzaka Zaki Syahansyah; Hesty Prima Rini (MANAJEMEN DEWANTARA, 2025)
This study aims to analyze the effect of work engagement on employee performance, with job satisfaction as a mediating variable among Herbalife supervisors in Gresik. A quantitative approach was employed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with the SmartPLS 3.0 application. Data were collected from 93 supervisors selected through simple random sampling, using a 5-point Likert scale questionnaire to measure work engagement, job satisfaction, and employee performance. The results show that work engagement has a positive and significant effect on employee performance. Furthermore, job satisfaction significantly strengthens the relationship between work engagement and employee performance. These findings suggest that supervisors with high levels of work engagement tend to experience greater job satisfaction, which in turn positively impacts their performance. This study recommends that direct selling companies enhance programs that support work engagement and job satisfaction to help achieve business goals.